Synthesis and Characterisation of Cobalt(II), Nickel(II), Copper(II), Zinc(II) and Cadmium(II) Complexes of N,N’-Propylene-bis(3-carboxypropenamide) - Babu, N. (Asian Journal of Chemistry, 2016)
Five complexes of Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) with a polydentate ligand N,N'-propylene-bis(3-carboxypropenamide) (PBCPH2) have been synthesized and characterized by elemental analysis, conductance and magnetic measurements, infrared spectral, NMR, electronic spectra, X-ray diffraction and thermal analysis. Composition of the complexes other than Cu(II) is [ML] and for Cu(II) it is [CuL]·2H2O, where L = [PBCP)2. In these complexes the ligand acts as a tetradentate.